Penghimpunan Dana Zakat Dan Faktor Penghambatnya - Mulvi Aulia (Jurnal Al-Mizan, 2020)
Zakat is a form of worship of Muslims, zakat is also a source of state income in the perspective of Islamic economics. In Indonesia the official amil zakat institution has been running for more than two decades. The collection of zakat funds starts from the movement of charity boxes to use digital technology. In struggling in the world of amil zakat, these institutions have shown improvements every year. The average growth of zakat collected through the official amil zakat body over the past 3 years is 23.3%. The National Gross Increase in Indonesian Products has consistently grown at around 5%. This shows that the level of awareness of the people affected by the obligatory zakat (Muzakki) in distributing zaktnya to the official amil zakat institutions is getting better. Management Management of zakat is also the case, collection of zakat funds has very diverse ingredients. But according to some experts the collection of zakat funds is still far from its potential, and even then it has been reduced through the assumption of a number of non-halal sources and the number of muzakki in Indonesia.